Unravelling the intersections of power: The case of sexual and reproductive freedom in the Philippines. (November 2015) - Tanyag, Maria
Synopsis: This article examines the political contestations over sexual and reproductive rights reform in the Philippines from an intersectional perspective. Specifically, it considers the Reproductive Health (RH) Bill which was enacted in 2012 to unpack the various competing interests and identities of coalitions that are mobilised by sexual and reproductive freedom in the Philippines. It demonstrates how the distinct reform agenda contained in the RH Bill is a direct outcome of the power differentials between and within coalitions. This suggests that the bill serves to benefit some at the expense of others based on how different actors are situated within the intersections of class, gender, sexuality, religion and nation. Data for this research comes from the triangulation of various sources including semi-structured interviews, the RH bill text, and official government and non-government publications. The case of the RH Bill in the Philippines highlights the interdependence between the recognition of sexual and reproductive freedom as a human right and the redistribution of power and resources in society. Highlights: Uses intersectionality to reveal multiple dimensions to contestations surrounding sexual and reproductive freedom in the Philippines. Highlights the dynamics between and within the coalitions that promote or oppose sexual and reproductive freedom. Draws attention to reform agendas and their exclusions based on class, gender, religion, nation, and sexuality. Illustrates the political and economic roots of Catholic fundamentalism through conservative elites. Critiques the perpetuation of a heteronormative sexual and reproductive rights agenda.